2014
DOI: 10.1074/jbc.m114.594721
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Phosphoribosyltransferase Promotes Epithelial-to-Mesenchymal Transition as a Soluble Factor Independent of Its Enzymatic Activity

Abstract: Background: Nicotinamide phosphoribosyltransferase (NAMPT) acts both as an enzyme in the production of the coenzyme NAD ϩ and as a secreted cytokine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 51 publications
4
55
0
Order By: Relevance
“…This finding is consistent with previous studies [35,36]. Involvement of different mechanisms have been reported in extracellular visfatin-mediated breast cancer growth and metastatic potential including cyclin D1 and cyclindependent kinase 2 (CDK2) [35], NF-κB and Notch1 [37], (transforming growth factor β (TGF-β) [38] or c-Abl and STAT3 signaling [36] pathways. Here we showed that PI3K/AKT and MAPK/ERK pathways are important regulators in visfatin-induced proliferation of breast cancer cells such that inhibition of PI3K and MEK1/2 blocked cell proliferation that was enhanced by visfatin.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies [35,36]. Involvement of different mechanisms have been reported in extracellular visfatin-mediated breast cancer growth and metastatic potential including cyclin D1 and cyclindependent kinase 2 (CDK2) [35], NF-κB and Notch1 [37], (transforming growth factor β (TGF-β) [38] or c-Abl and STAT3 signaling [36] pathways. Here we showed that PI3K/AKT and MAPK/ERK pathways are important regulators in visfatin-induced proliferation of breast cancer cells such that inhibition of PI3K and MEK1/2 blocked cell proliferation that was enhanced by visfatin.…”
Section: Discussionsupporting
confidence: 93%
“…S3E and S3F). Other mechanisms reported in extracellular visfatin-mediated breast cancer growth and metastatic potential included cyclin D1 and cdk2 (44), NF-kB and Notch1 (45), or PI3K/Akt and TGFb (46). As the identity of "visfatin receptor" is not known to date, it limits our understanding for the molecular mechanisms of extracellular visfatin.…”
Section: Characterization Of the Biologic Effect Of Visfatin On Breasmentioning
confidence: 94%
“…28 So the nonenzymatic action mode of extracellular NAMPT still remains to be exactly elucidated because numerous studies have reported that extracellular NAMPT is able to regulate cell events such as macrophage survival/polarization and epithelial-to-mesenchymal transition by an enzyme activity-independent manner. [38][39][40] …”
Section: Nampt and Nampt-controlled Nad Poolmentioning
confidence: 98%